Salvage of an Infected Periprosthetic Failed Fracture Fixation in a Nonagenarian - Jennifer Hagen MD; Howard Chansky MD; Sean E. Nork MD; Lisa A. Taitsman MD, MPH (Geriatric Orthopaedic Surgery & Rehabilitation, 2013)
Infected nonunions resulting in segmental bone loss are a devastating complication for patients and a difficult problem for surgeons. Adequate soft tissue coverage, return of mobility, fracture stability, and long-term freedom from infection are all important goals of treatment. Although there are numerous published studies that provide some treatment guidelines, there are patients who require unique and individualized solutions. In this report, we present a case in which an antibiotic-impregnated cement spacer was used as a component of the definitive treatment in a geriatric patient with segmental bone loss of the femur secondary to severe infection as a salvage technique to avoid amputation.